Hubungan Gangguan Penglihatan dan Faktor Lain Dengan Fungsi Kognitif Pada Lansia di Indonesia - Thiantoro, Benedicta Ann Clarabelle; Turana, Yuda; Handajani, Yvonne Suzy (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Introduction: Vision impairment is one of the most common problems experienced by the elderly.Vision impairment may disturb an elderly’s well-being. Various studies have found significant correlationbetween hearing loss and cognitive function. Data is now available from the Indonesian Family Life Survey(IFLS). However, there is limited research in the association between vision impairment and cognitive functionand no studies have used IFLS-5 data on this topic.Aim: To evaluate the association between vision impairment and other factors with cognitive dysfunctionin Indonesia’s geriatric population.Methods: This study is a descriptive analytic study utilizing data from 2375 seniors of 60 years old andover from the fifth wave of Indonesian Family Life Survey (IFLS-5). Analysis is done through univariate, bivariate,and multivariate analysis.Results: The majority of respondents are male (82,7%), married (76,5%), living in urban areas (52,3%),and has <9 years of education (57,1%). 9,4% respondents experienced vision impairment, 13,4% experiencedADL impairment, 34,3% experienced IADL impairment, and 49,3% experienced cognitive impairment. Inbivariate analysis, marital status (p=0,004), residence (p<0,001), education (p<0,001), IADL (p<0,001), andvision impairment (p=0,049) are significantly correlated with cognitive function. In subanalysis, the use ofreading glasses in elderly with vision impairment is significantly correlated with cognitive function. Inmultivariate analysis, residence (p=0,002), education (p<0,001) and IADL (p=0,023) are significantly correlatedwith cognitive function.Discussion: Residence, education, and IADL is significantly associated with cognitive function. Visionimpairment is not significantly associated with cognitive function.Keywords: Cognitive Function, Geriatric, IFLS-5, Vision Impairment